Synthesis and Biological Screening of 1,3-Dialkyl Derivatives of 4-(2’5-Dioxopyrrolidine-3-yl) Phenyl Sulphinic Acid as Inhibitors of Oestrone Sulphatase: Steroid sulphatase Inhibitor - Hassanzadeh, Farshid; Smith, H. John; J. Nicholls, Paul (Iranian Journal of Pharmaceutical Sciences, 2006)
1,3-dialkyl 3-phenylpyrrolidine-2, 5-diones were modified to produce potential steroid sulphatase inhibitors. These modifications were aimed at producing compounds, which could be expected to bind reasonably well to the active site of the steroid sulphatase enzyme but could not be hydrolyzed readily by the enzyme due to the covalent S-C bond present. In this regard the sulphinic acid derivatives of di-substituted 3-phenylpyrrolidine-2, 5-diones were prepared. On biological testing, only compound 4-(2,5-dioxo-1, 3-dipentylpyrrolidine-3-yl) phenylsulphinic acid (F5) was found to be an inhibitor of the steroid sulphatase enzyme from human placenta and was about twice as potent as the known inhibitor danazol.